Comparison of Physical Activity and Sedentary Behaviour Patterns by Sex, Geographical Location, and Time of the Week in Mexican Adolescents - Edtna Jáuregui-Ulloa; Julissa Ortiz-Brunel; Alejandro Gaytan-Gonzalez; Raúl Soria-Rodríguez; José Marcos Pérez-Maravilla; Martín Francisco González-Villalobos; Deborah Salvo; Darren E. R. Warburton; Juan Ricardo López-Taylor (Journal of Functional Morphology and Kinesiology)
Background: Excess sedentary behaviour (SB) and insufficient physical activity have been identified as risk factors for cardiometabolic diseases in adolescents, and some factors may affect how much time they spend on these activities. This study sought to compare the SB and PA patterns as well as compliance with PA recommendations by sex, geographical location, and time of the week in Mexican adolescents. Methods: In a cross-sectional design, we objectively assessed SB and PA in 106 adolescents (15 to 18 y) through waist-worn accelerometers for one week. The time spent in SB and in PA at different intensities was compared by sex, geographical location and time of the week with two-way and three-way repeated measures MANOVAs, while the compliance with physical activity recommendations (i.e., ≥60 min/day) was compared using chi-squared and McNemar tests. Results: Male participants spent more time in moderate, vigorous, and moderate to vigorous PA than females both during the whole week and on weekdays (all p < 0.05). There was no significant difference in SB nor PA by geographical location (i.e., metropolitan vs. non-metropolitan areas). Moreover, all participants spent more time on moderate, vigorous, and moderate to vigorous PA on weekdays than on weekends (p < 0.05). Compliance with international PA recommendations also showed a sex difference (males > females) and change between weekdays and weekends with no difference by geographical location. Conclusions: While geographical location does not seem to be a relevant factor, sex and time of the week appear to influence the SB and PA patterns in Mexican adolescents.